2014
DOI: 10.1002/cncr.28792
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and intermediate phenotypic susceptibility markers of gastric cancer in Hispanic Americans: A case‐control study

Abstract: BACKGROUND: Hispanics are the largest nonwhite ethnic group in the US population, and they have higher incidence and mortality rates for gastric cancer (GC) than whites and Asians. Studies have identified several genetic susceptibility loci and intermediate phenotypic biomarkers for GC in whites and Asians. No studies have evaluated genetic susceptibility and intermediate phenotypic biomarkers in Hispanics. METHODS: In a case-control study of 132 Hispanic patients with GC (cases) and a control group of 125 His… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 60 publications
2
23
0
Order By: Relevance
“…The studied cancer type included gastric cancer [8, 14-17, 20-22, 25, 26, 31, 32, 34, 39, 41-43], bladder cancer [9, 18, 23, 28, 35, 40], prostate cancer [19], esophageal cancer [20, 33], breast cancer [24], colorectal cancer [27], and gallbladder cancer [29, 30]. In term of ethnicity, 21 studies were performed among Asians, 10 studies among Caucasians, and one study among Africans.…”
Section: Resultsmentioning
confidence: 99%
“…The studied cancer type included gastric cancer [8, 14-17, 20-22, 25, 26, 31, 32, 34, 39, 41-43], bladder cancer [9, 18, 23, 28, 35, 40], prostate cancer [19], esophageal cancer [20, 33], breast cancer [24], colorectal cancer [27], and gallbladder cancer [29, 30]. In term of ethnicity, 21 studies were performed among Asians, 10 studies among Caucasians, and one study among Africans.…”
Section: Resultsmentioning
confidence: 99%
“…Obesity has been associated with the development of various cancers of the gastrointestinal tract, including gastric cancer (27), and with obesity rates on the rise in the young (28), this may increase rates of gastric cancer. Third, genetic susceptibility also merits consideration as a recent case-control study identified the presence of certain single nucleotide polymorphisms as loci for susceptibility to gastric cancer in Hispanic Americans (29). Finally, differences in tumor biology may also be implicated as Hispanics have previously been shown to have increased incidence of mucinous/signet cell histology, involvement of the whole stomach, and peritoneal dissemination (30).…”
Section: Discussionmentioning
confidence: 99%
“…Two case‐control studies have reported the relationship between mtDNA copy number in leukocyte and gastric cancer risk to date. Sun et al conducted a study in 132 gastric cancer cases and 125 controls of a Hispanic population and found significant association between low mtCN and increased gastric cancer risk (OR = 11.00; 95%CI = 4.79‐25.23), when individuals were dichotomized into high and low mtCN groups based on the median mtCN value in the controls. They also examined the association of leukocyte telomere length with the risk of gastric cancer, and found no significant association between short telomere length and increased gastric cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…However, the association between mtCN and gastric cancer remains conflicting. Pilot data from a recent retrospective case‐control study in Hispanic Americans showed that low mtCN was associated with increased risk of gastric cancer . Yet, a prospective study of Chinese women found no association between leukocyte mtCN and risk of gastric cancer …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation